2015
DOI: 10.1016/j.polymdegradstab.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Aging mechanisms in RTV polysiloxane foams

Abstract: a b s t r a c tThe long-term use of polysiloxane foams requires a good understanding of the diverse factors that may influence their performance. The aim of the present work was to understand the interplay between inservice environments and reactive species that reside in the foams. Two foams (SX358 and S5370) were thermally aged under compressive strain to gauge the onset of compression set, an indicator of degradation. Experiments were performed by either aging the foams in open air containers or in high hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Despite the plethora of research conducted on PDMS and PDMS composites, there has been much less focus on investigating how the performance of Sylgard 184 changes over time. Some work examining how aged Sylgard changes includes thermally aging chemically modified Sylgard 184 [ 27 ], UV-aging PDMS insulation [ 28 ], thermally aging resin-filled PDMS elastomers [ 29 ], humidity-aging siloxane foams [ 30 , 31 ], and gamma irradiation-aging silicones [ 32 ]. Natural and induced aging can lead to device or application failure and could potentially introduce new hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the plethora of research conducted on PDMS and PDMS composites, there has been much less focus on investigating how the performance of Sylgard 184 changes over time. Some work examining how aged Sylgard changes includes thermally aging chemically modified Sylgard 184 [ 27 ], UV-aging PDMS insulation [ 28 ], thermally aging resin-filled PDMS elastomers [ 29 ], humidity-aging siloxane foams [ 30 , 31 ], and gamma irradiation-aging silicones [ 32 ]. Natural and induced aging can lead to device or application failure and could potentially introduce new hazards.…”
Section: Introductionmentioning
confidence: 99%
“…As conclusion, the main mechanism of radiolysis in their radiation conditions is the crosslinking stage. Labouriau et al 131 also studied thermal aging under compressive strains of diatomaceous earth-filled polysiloxane foams in the presence or absence of humidity. Foam morphologies of these foams and compositions are described in Patterson et al 132 Foams aged in the presence of humidity showed higher compression set than foams aged in the open-air environment.…”
Section: H 2 and Other Gasmentioning
confidence: 99%
“…Foam morphologies of these foams and compositions are described in Patterson et al 132 Foams aged in the presence of humidity showed higher compression set than foams aged in the open-air environment. According to Labouriau et al, 131 some active catalysts left from the curing step may enable post-curing reactions such as hydrolysis and rearrangement of the network.…”
Section: H 2 and Other Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, research work on the aging behaviors and mechanisms of PDMS rubber exposed to radiation, temperature, and mechanical load has been reported, especially on the coupling effect of radiation and other environmental factors 7,[9][10][11] . The quantitative analysis of the chemical reaction was conducted by Fourier transform infrared spectroscopy (FTIR) 12,13 , nuclear magnetic resonance (NMR) measurement 14 , thermogravimetric analysis (TGA) 15 , and pyrolysis gas chromatography-mass spectrometry (Py-GC/MS) 16 , etc. The types of aging products, such as crosslinking and chain scission, during the aging process were indirectly identified by these experimental measures 17,18 .…”
Section: Introductionmentioning
confidence: 99%